The efficacy of community-based exercise programs on circulating irisin level, muscle strength, cardiorespiratory endurance, and body composition for ischemic stroke: a randomized controlled trial - Kang, Dongheon; Park, Jiyoung; Eun, Seon-Deok (Frontiers in Neurology, 2023)
Objective We investigated the changes in circulating irisin levels after community-based exercise and the association of these levels with improvements in muscle strength, cardiorespiratory endurance, and body composition in people with ischemic stroke. Methods Twenty participants were randomly assigned to either a control or an exercise group. The community-based exercise program (CEP) consisted of 8 weeks of 1 h sessions for 3 days a week. Irisin levels, muscle strength, cardiorespiratory endurance, and body composition were assessed before and after the intervention. Results Significant improvements were observed in the leg and trunk strength, peak oxygen consumption values, and body composition of the exercise group compared with the control group. In addition, circulating irisin levels were observed to have increased in the exercise group, positively correlated with muscle strength and cardiorespiratory endurance. Conclusion CEP might be an effective intervention to increase irisin levels and prevent a stroke-related decline in muscle function.